Uma aplicação da técnica de cenários para a indústria de autopeças de veículos de passageiros e comerciais leves movidos por motor a combustão interna no Brasil: potenciais cenários para a indústria automotiva frente à possível adoção dos veículos elétricos - D’Andrea Mateus, José Carlos (2021)
The automotive industry has developed its business model centered on vehicles powered by internal combustion (MCI). From the 1960s onwards, with the growth of movements in favor of the control of pollutant emissions, new demands for safer vehicles and with lower levels of greenhouse gas (GHG) emissions emerged. Since then, the industry resumes the development of electric vehicles (EV). But only at the beginning of the 21st century is there a consistent process of change and restructuring in the automotive sector, which drives global transformations in this industry. Opportunities arise for the transition from an internal combustion-powered vehicle (MCI) to an electric one. The objective of this study is to identify uncertainties and possible scenarios with a horizon over the next 20 years of the current Brazilian automotive industry (IAB). The analysis considers the transition from combustion engines to an electrified future. It was decided to use the Schwartz method: critical uncertainties were addressed and analyzed and, based on the data obtained, prospective scenarios were constructed.